2015
DOI: 10.1007/s10562-015-1632-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties of Hierarchical Mordenite Nanosheets Synthesized by Self-Assembly Between Subnanocrystals and Organic Templates

Abstract: An effective and rapid procedure to synthesize hierarchical MOR (Hi-MOR) nanosheets by self-assembly between subnanocrystals and organic templates was reported. The hierarchical pore systems provided a large quantity of Brønsted acid sites. Compared with conventional mordenite, Hi-MOR showed higher activity, xylene selectivity and longer catalytic life in the reaction of toluene disproportionation, thanks to its excellent diffusion from hierarchical structure. Graphical Abstract Hierarchical morednite (Hi-MOR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…In comparison to material synthesized in the absence of CTAB and PEG, a higher amount of both Brønsted and Lewis acid sites is present within the hierarchical pore system. Accordingly, nanosheet MOR material exhibits higher activity, xylene selectivity, and longer catalyst lifetime in the toluene disproportionation reaction [242]. The PEG has acted as a mesopore generation agent in the formation of a set of hierarchical MOR catalysts with enhanced crystallinity and a higher quantity of strong acid sites in comparison to the reference zeolite obtained without PEG [243].…”
Section: T3 T4mentioning
confidence: 99%
“…In comparison to material synthesized in the absence of CTAB and PEG, a higher amount of both Brønsted and Lewis acid sites is present within the hierarchical pore system. Accordingly, nanosheet MOR material exhibits higher activity, xylene selectivity, and longer catalyst lifetime in the toluene disproportionation reaction [242]. The PEG has acted as a mesopore generation agent in the formation of a set of hierarchical MOR catalysts with enhanced crystallinity and a higher quantity of strong acid sites in comparison to the reference zeolite obtained without PEG [243].…”
Section: T3 T4mentioning
confidence: 99%
“…Generally, organosilanes and mono‐ or multi‐quaternary ammonium salts have been employed to introduce mesoporosity in MOR zeolite. Nearly all of the described recipes involve the addition of a mesoporogen to a synthesis mixture which contains seeds, conventional SDAs, or require complex cationic surfactants with two or more ammonium ions . There are only few reports that claim the formation of hierarchical MOR zeolite with a mono‐quaternary ammonium surfactant or aniline as a single SDA .…”
Section: Introductionmentioning
confidence: 99%
“…[276] Next to nanorods, nanosheets can be synthesized as well. This was done by Wang et al [277] and Liu et al [278] who both employed PEG as template in the hydrothermal synthesis, however, Liu et al also used CTAB as an additional template. It was shown that the use of PEG dramatically increased the crystallinity compared to reference mordenites that were synthesized without the addition of PEG.…”
Section: Nanozeolites and Their Assemblymentioning
confidence: 99%
“…[ 277 ] and Liu et al. [ 278 ] who both employed PEG as template in the hydrothermal synthesis, however, Liu et al. also used CTAB as an additional template.…”
Section: Synthesis Of Hierarchical 12‐mr Zeolitesmentioning
confidence: 99%